Adaptación de un protocolo para evaluar el bienestar animal en bovinos lecheros de Colombia (2022)
The agricultural sector is changing vertiginously, due to global trends in globalization, internationalization of markets and multinational trade agreements (Zapata, 2016). Colombia is the fourth largest milk producing country in South America, surpassed by Brazil, Mexico and Argentina, and the Colombian livestock industry is growing (Fedegan, 2018). One of the emerging issues in this scenario is animal welfare (Zapata, 2016). Every day, the animal welfare of production animals becomes more important, the consumer concerned about how the animals from which the food they consume are kept (Trillo, Vigo, Barrio, Becerra, Garcia and Quintela. 2015)